Pendidikan Multikultural Di SDIT 2 Daarussalaam dan SMPIT Daarussalaam Sangatta Utara - Anisa Nur Azizah Anisa; Muhammad Yasin (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2026)
This study aims to examine the implementation of Multikultural education at SDIT 2 Darussalaam and SMPIT Daarussalaam Sangatta using a qualitative approach. The research focuses on three main aspects: (1) the implementation of Multikultural educatio at SDIT 2 Daarussalaam and SMPIT Daarussalaam, (2) school policies supporting Multikultural values at SDIT 2 Daarussalaam and SMPIT Daarussalaam, and (3) the challenges and efforts in its implementation at SDIT 2 Daarussalaam and SMPIT Daarussalaam . The findings indicate that SDIT 2 Daarussalaam applies Multikultural education conceptually through thematic learning, while SMPIT Daarussalaam implements it more practically through habituation and collaborative activities. Both schools support tolerance-based values through character-building programs and the integration of Islamic teachings grounded in rahmatan lil ‘alamin. The main challenges include a homogeneous school environment and limited interfaith interaction; however, these are addressed through character education, social activities, and teacher role modeling, which effectively foster inclusive and tolerant attitudes among students.